Characteristics of Rice Analog from Composite Flour (Mocaf: Sago: Soybean: Moringa Leaf) with Addition of Carrageenan - Jariyah Jariyah; Alodia Vestra (Jurnal Teknologi Hasil Pertanian, 2023)
Analog rice is an alternative food to replace rice using sago, sorghum, or even corn with carbohydrate content near or exceeds the rice and the shape. Analog rice made from mocaf flour has a lower protein content than milled rice, so it is necessary to add soy flour which has 35.00% of protein content, sago flour which has 21.38% of amylose content, and Moringa leaves flour which has an antioxidant activity of 32.96%. Carrageenan is also added to the mixture as a binder. The aim of the study was to determine the effect of the proportions of composite flour (mocaf: sago: soybean: moringa leaves) with the addition of carrageenan on the characteristics of analog rice. Completely randomized factorial design was used in this study with the first factor proportion of mocaf: sago: soybean: moringa leaves flour such as A (70: 10: 20: 3.5gr), B (60: 20: 20: 3.5 gr), and C (50: 30: 20: 3.5gr) with the second factor the addition of carrageenan (2, 3 and 4%). The data were analyzed using Minitab V.17, with 5% DMRT (Duncan Multiple Range Test). The best results for analog rice were obtained from proportion A (70: 10: 20: 3.5 gr) with the addition of 3% carrageenan with characteristics 3.22% of moisture, 2.83% of ash, 145.33% of rehydration power, 106.25% of swelling volume and 12.5% of antioxidant activity, with organoleptic score 3.10 of taste, 3.55 of colour; 3.38 of flavor; and 3.10 of texture.